1991
DOI: 10.1099/0022-1317-72-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Differentiation of Potyvirus Isolates and Identification of Strain-, Virus-, Subgroup-specific and Potyvirus Group-common Epitopes Using Monoclonal Antibodies

Abstract: A panel of monoclonal antibodies (MAbs) generated against an admixture of 12 potyvirus isolates was used to compare and differentiate diverse potyviruses. Both native and denatured virions of strains of bean yellow mosaic (BYMV), potato virus Y, tobacco etch, pea seed-borne mosaic, iris severe mosaic, iris mild mosaic and asparagus virus-1 potyviruses were used as immunogen and as antigen for screening of the hybridoma cell lines. Thirty cell lines secreting potyvirus-specific antibodies reactive in indirect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…Similarly, previous studies showed an all-ornone reaction that completely abolished the reactivity because of substitutions of critical residues in the protein (24). Previous studies on mapping epitopes of plant viruses used mutants with single or double amino acid substitutions in the coat protein (25), deletion mutants ofthe coat protein (26,27), and short peptide fragments expressed in E. coli as fusion protein or free protein (28,29). Our results provide direct molecular evidence for the critical role of a single nucleotide alteration and the resulting change in the codon on the reactivity of a monoclonal antibody with severe isolates of a plant virus.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, previous studies showed an all-ornone reaction that completely abolished the reactivity because of substitutions of critical residues in the protein (24). Previous studies on mapping epitopes of plant viruses used mutants with single or double amino acid substitutions in the coat protein (25), deletion mutants ofthe coat protein (26,27), and short peptide fragments expressed in E. coli as fusion protein or free protein (28,29). Our results provide direct molecular evidence for the critical role of a single nucleotide alteration and the resulting change in the codon on the reactivity of a monoclonal antibody with severe isolates of a plant virus.…”
Section: Discussionmentioning
confidence: 81%
“…The fact that, by using the appropriate screening technique, we were able to identify common epitopes between viruses for which little or no serological relationship has been demonstrated, together with the broad spectrum tests which have been produced recently for potyviruses (Jordan & Hammond, 1991 ;Shukla et al, 1989), and to some extent for luteoviruses (Murphy & D'Arcy, 1991), opens the way for the development of MAbs with a broader spectrum for other virus groups. These will prove to be very useful tools for quarantine testing.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, certain MAbs that are also raised against native virions such as TEV (44) or JGMV (42) cross-react with other potyviruses. However, mixtures of native and denatured virions of 12 potyvirus isolates have been used for immunization, leading to identification of a broad-spectrum PTY1 MAb from 30 screened MAbs that detects at least 55 potyvirus isolates (52). In contrast, we chose a recombinant protein for use as an immunogen, which was formed by fusion of three conserved core CP regions instead of from virus particles; therefore, we avoided the screening of MAbs that react to species-specific epitopes at the N or C terminus and also increased the opportunity for induction of broad-spectrum MAbs.…”
Section: Discussionmentioning
confidence: 99%
“…2B and 3B), suggesting that the epitope reacting with this C4 MAb should be sequential and not conformational. Jordan and Hammond have proposed that the epitope type may be determined by I-ELISA and triple antibody sandwich (TAS)-ELISA with disrupted and intact virions, respectively (52). MAbs that react best with plate-trapped, disrupted virus particles and CP subunits, as demonstrated by I-ELISA, recognize antigenic sites as cryptotopes, which are hidden within the intact virion (52).…”
Section: Discussionmentioning
confidence: 99%